2022
DOI: 10.3390/nano12152600
|View full text |Cite
|
Sign up to set email alerts
|

Control of the Drying Patterns for Complex Colloidal Solutions and Their Applications

Abstract: The uneven deposition at the edges of an evaporating droplet, termed the coffee-ring effect, has been extensively studied during the past few decades to better understand the underlying cause, namely the flow dynamics, and the subsequent patterns formed after drying. The non-uniform evaporation rate across the colloidal droplet hampers the formation of a uniform and homogeneous film in printed electronics, rechargeable batteries, etc., and often causes device failures. This review aims to highlight the diverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 179 publications
0
4
0
Order By: Relevance
“…As many processes dealing with colloidal particle suspensions are performed under dynamic environment [24,25], observation under such an environment should be useful. The combination of a confocal/optical microscope and rheometer is a good option to study concentrated colloidal systems under shear application [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…As many processes dealing with colloidal particle suspensions are performed under dynamic environment [24,25], observation under such an environment should be useful. The combination of a confocal/optical microscope and rheometer is a good option to study concentrated colloidal systems under shear application [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…3 In this regard, evaporationdriven self-assembly has become an effective method for the controllable patterning of nanoparticles. 4 The pinned contact line of an evaporating sessile droplet induces a capillary flow, which causes liquid from the interior part of the droplet to replenish the escaped mass along the three-phase contact line, 5,6 and the higher evaporation rate near the contact line can also enhance this compensatory flow. 7,8 The evaporation-induced flow inside colloidal droplets can deposit CNTs and align them along the contact line.…”
Section: Introductionmentioning
confidence: 99%
“…Evaporation of the volatile solvent usually leads to various deposited patterns. Unveiling the formation mechanism is very challenging because the solvent evaporation is a nonequilibrium dynamic process and is usually associated with complex internal flows. Past experiments have made great effort in colloids, , liquid crystals, , and various suspensions. , For example, Deegan , revealed that the capillary flow can transport solutes from the center of a droplet to the evaporating edge, which creates the well-known “coffee rings”. Shao et al showed that the Marangoni flow can align the rod-like cellulose nanocrystals at liquid–air–substrate contact line, leading to concentric deposited pattern with Maltese cross.…”
Section: Introductionmentioning
confidence: 99%